2022
DOI: 10.21511/bbs.17(1).2022.01
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting non-performing loans in commercial banks of selected West African countries

Abstract: This paper examines the macro-economic and bank-specific factors affecting non-performing loans in commercial banks. Using 47 listed commercial banks from six countries, namely 19 banks from Nigeria, 14 banks from Benin, 3 banks from Burkina Faso, 3 banks from Gambia, 3 banks from Guinea, and 5 banks from Liberia for the period 2008 to 2019, fixed and random effect model was used. The Hausman test favored the selection of fixed effect model, and it was found from the estimation that the liquidity ratio, capita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…, 2019; Nwosu et al. , 2020; Msomi, 2022). Hence, whilst the clients have gotten away with their influence, they could hurt shareholders and the national economy in the long run.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…, 2019; Nwosu et al. , 2020; Msomi, 2022). Hence, whilst the clients have gotten away with their influence, they could hurt shareholders and the national economy in the long run.…”
Section: Discussionmentioning
confidence: 98%
“…It could be suggested that clients would always try to get the best deal out of every business relationship if the opportunity presents itself, particularly where incentives such as dependence on property performance for bonus payments exist (Crosby and Devaney, 2019) (Central Bank of Nigeria, 2023;Focus Economics, 2023), thereby creating enormous incentives for loan-seeking customers to apply every tactic to obtain a favourable valuation outcome. These behaviours of clients and loan-seeking customers, however, are inimical as there is a retinue of literature that points to the fact that financial institutions in Nigeria battle with non-performing loans, which affects their profits, financial performance and the Nigerian economy (Morakinyo and Sibanda, 2016;Okoh et al, 2019;Nwosu et al, 2020;Msomi, 2022). Hence, whilst the clients have gotten away with their influence, they could hurt shareholders and the national economy in the long run.…”
Section: Discussionmentioning
confidence: 99%
“…When inflation increases, banks must raise deposit interest rates to attract deposits, while not being able to sharply increase lending interest rates correspondingly. The down economic context when high inflation causes businesses' demand for loans in production to decrease, reducing the bank credit growth (Msomi, 2022), which negatively affects bank profit margins.…”
Section: Discussionmentioning
confidence: 99%
“…The interest rate is a significant factor in influencing the rate of NPL in banks, as high-interest rates erode borrowers' ability to repay their debts, leading to an increase in defaulters. Studies have shown a positive association between interest rates and NPLs, including those by (Farhan et al, 2012), Abolhasani et al (2022), Al Masud and Hossain (2020), Wood and Skinner (2018), Msomi (2022) and Kuutol et al (2015). Real interest rates, which are adjusted for inflation, have also been found to positively influence NPLs.…”
Section: 24mentioning
confidence: 94%